2024
DOI: 10.3390/jof10030174
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Arbuscular Mycorrhizal Fungi (AMF) and Grass Endophyte (Epichloë) on Host Plants: A Review

Youlei Shen,
Tingyu Duan

Abstract: In nature, plants frequently experience concurrent colonization with arbuscular mycorrhizal fungi (AMF) and grass endophytes (Epichloë). These two fungi assist in mineral uptake and stress tolerance by the host. Despite the abundance of recent studies exploring the individual functions of these fungi in diverse ecosystems, research on the effects of the interaction between these two symbiotic fungi on the host, particularly in agricultural production and ecological conservation. This review provides an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
0
2
1
Order By: Relevance
“…The manner in which arbuscular mycorrhizal (AM) fungi colonize plant roots remains poorly understood. It is believed that the excretion of compounds from plant roots significantly enhances the colonization of roots by mycorrhizal fungi, making the identification of these compounds crucial for understanding the mechanisms underlying root mycorrhizal colonization [29]. Despite previous reports and speculations about the negative effects of stress on colonization rates [30], combined B and salt stress did not affect the AMF colonization rate in our experiment (Figure 7b).…”
Section: Detrimental Effects Of Combined B and Salt Stress On Maize P...contrasting
confidence: 68%
“…The manner in which arbuscular mycorrhizal (AM) fungi colonize plant roots remains poorly understood. It is believed that the excretion of compounds from plant roots significantly enhances the colonization of roots by mycorrhizal fungi, making the identification of these compounds crucial for understanding the mechanisms underlying root mycorrhizal colonization [29]. Despite previous reports and speculations about the negative effects of stress on colonization rates [30], combined B and salt stress did not affect the AMF colonization rate in our experiment (Figure 7b).…”
Section: Detrimental Effects Of Combined B and Salt Stress On Maize P...contrasting
confidence: 68%
“…Current research trends and advancements in the study of plant beneficial symbionts involve various techniques and approaches. These include analyzing plant microbiomes, studying the genes encoded by plant growth-promoting bacteria (PGPB) through DNA genome sequencing, and investigating gene expression using transcriptomics, proteomics, and metabolomics [78,79]. Additionally, researchers are exploring the use of genome editing to modify PGPB, encapsulating PGPB inoculants for plant treatment, and imaging techniques to visualize plant-bacteria interactions [79].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…These include analyzing plant microbiomes, studying the genes encoded by plant growth-promoting bacteria (PGPB) through DNA genome sequencing, and investigating gene expression using transcriptomics, proteomics, and metabolomics [78,79]. Additionally, researchers are exploring the use of genome editing to modify PGPB, encapsulating PGPB inoculants for plant treatment, and imaging techniques to visualize plant-bacteria interactions [79]. The study of symbiotic partners through transcriptome analysis has revealed the modulation of gene expression and unique functional metabolic pathways in symbionts [80].…”
Section: Future Perspectivesmentioning
confidence: 99%